INTERAKSI KOMPONEN SUSTAINABLE LIVELIHOOD MEMENGARUHI PILIHAN PENGGUNAAN AIR BERSIH PADA KOMUNITAS URBAN DI KAWASAN PERMUKIMAN KUMUH: INTERACTION OF SUSTAINABLE LIVELIHOOD COMPONENT INFLUENCES SELECTION OF CLEAN WATER USAGE IN URBAN COMMUNITY IN SLUM SETTLEMENT AREA - Abadi, Moh. Fairuz (Bali Medika Jurnal, 2018)
Background. Clean waters become a daily needs of healthy and productive life. Slums are densely populated urban area which is closely related to problems of urbanization and poverty. The purpose of this paper is to review research related to the five capital of Sustainable livelihood assets: namely human, social natural, financial and physical capital for access of clean water in urban slum communities. Methods, using literature review, inclusion criteria, are all of studies that have been conducted in the period 2009-2014, the water supply policy and social determinants. On the PubMed found 329 and at Ebsco Host 176 research articles. The selection are based on criteria found 10 articles in PubMed and 10 on Ebsco Host. Results. The study are come from many cities that representing of the Americas, Europe, Asia, Africa, and Australia. Sustainable livelihood capital does not stand alone, the interaction of capital influences the choice of water use. High illiteracy and dropout becomes a limiting factor in human and financial capitals. The natural capitals influenced by two factors, the change of seasons, and the high contamination. In social capital necessary to change the strategy of policy through strengthening community empowerment, social protection and social inclusion . Physical capitals are developed piping systems, supply of bottled water and recycle technology. Clean water access is also affected by local regulations and political.Conclusions. Clean water acces for urban slum communities affected by the interaction between the components of livelihood assets and also the policies. Key words Sustainable livelihood, water use, slum.